Colombia's narcotics nightmare: how the drug trade destroyed peace - Henderson, James D. (McFarland & Company, Inc., Publishers, 2015)
"This history of Colombia's illegal drug trade describes how in the late 1960s narcotics traffickers from the United States convinced Colombians who had no previous involvement in the drug trade to grow marijuana for export to America. By the early '70s, foreign (mostly American) traffickers began requesting cocaine"--